Impact of remaining kidney volume to body weight ratio on renal function in living kidney donors. Issue 4 (11th March 2016) - Song, Turun; Rao, Zhengsheng; Qiu, Yang; Liu, Jinpeng; Huang, Zhongli; Wang, Xianding; Lin, Tao
Abstract: To investigate whether the ratio of remnant kidney volume to body weight (V/W ratio) can impact renal function in donors, 45 living kidney donors were enrolled. Kidney volume was analyzed by magnetic resonance imaging. Renal function was compared between donors with a V/W ratio of < 2.0 mL/kg ( n = 23) or ≥ 2.0 mL/kg ( n = 22). Donors in both V/W groups showed similar serum creatinine levels and estimated glomerular filtration rates (eGFRs) at 7 days and 1 year, whereas donors with a V/W ratio of < 2.0 mL/kg had significantly higher 24‐hour urine protein levels at 1 year (0.54 ± 0.23 g/d vs. 0.33 ± 0.19 g/d, p = 0.028). Multivariate analysis revealed no correlation between the V/W ratio and eGFR at 7 days or 1 year, and a V/W ratio of < 2 mL/kg was not associated with an increased incidence of eGFR < 60 mL/min/1.73 m 2 at 1 year (risk ratio 1.73, 95% confidence interval 0.10–29.47). The V/W ratio correlated inversely with 24‐hour urine protein ( r = −0.377, p = 0.021) at 1 year, and donors with a V/W ratio of < 2.0 mL/kg were more likely to show 24‐hour urine protein >300 mg (risk ratio 1.70, 95% confidence interval 1.08–2.67) at 1 year. Donors with lower V/W ratios have higher 24‐hour urinary protein levels at 1 year after transplantation. These findings suggest that the V/W ratio may be useful for kidney selection.